2022
DOI: 10.1038/s41385-022-00570-3
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine protection by Cryptococcus neoformans Δsgl1 is mediated by γδ T cells via TLR2 signaling

Abstract: We previously reported that administration of Cryptococcus neoformans Δsgl1 mutant vaccine, accumulating sterylglucosides (SGs) and having normal capsule (GXM), protects mice from a subsequent infection even during CD4+ T cells deficiency, a condition commonly associated with cryptococcosis. Here, we studied the immune mechanism that confers host protection during CD4+T deficiency. Mice receiving Δsgl1 vaccine produce IFNγ and IL-17A during CD4+ T (or CD8+ T) deficiency, and protection was lost when either cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 112 publications
(122 reference statements)
0
10
0
Order By: Relevance
“…In our previous studies, we found that C. neoformans Δ sgl1 and A. fumigatus Δ sgla are potent immune stimulators, and for C. neoformans Δ sgl1 , we showed that this immune activation is controlled by Toll-like receptor 2 (TLR2) on γ/δ T cells ( 28 ). Thus, both Cn Δ sgl1 and Af Δ sgla are exciting vaccine candidates, because they are highly effective in preventing a secondary infection either as live-attenuated or as heat-killed vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we found that C. neoformans Δ sgl1 and A. fumigatus Δ sgla are potent immune stimulators, and for C. neoformans Δ sgl1 , we showed that this immune activation is controlled by Toll-like receptor 2 (TLR2) on γ/δ T cells ( 28 ). Thus, both Cn Δ sgl1 and Af Δ sgla are exciting vaccine candidates, because they are highly effective in preventing a secondary infection either as live-attenuated or as heat-killed vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The γδ T cells appear to recognize C. neoformans directly via TLR2 and produce IFNγ and IL‐17A. Stimulation of γδ T cells with sgl1∆ containing a larger amount of SGs releases larger amounts of IFNγ and IL‐17A than stimulation with H99 or sgl1∆/cap59∆ (sgl1∆ lacking capsule), and the production is markedly reduced in γδ T cells lacking TLR2 23 . CAP59 is an essential gene for the biosynthesis of glucuronoxylomannan (GXM), the main component of capsules, and CAP59 ‐deficient strains lose GXM 46 .…”
Section: Whole‐cell Vaccines Using Cryptococcal Recombinant Strainsmentioning
confidence: 99%
“…Stimulation of γδ T cells with sgl1Δ containing a larger amount of SGs releases larger amounts of IFNγ and IL-17A than stimulation with H99 or sgl1Δ/ cap59Δ (sgl1Δ lacking capsule), and the production is markedly reduced in γδ T cells lacking TLR2. 23 CAP59 is an essential gene for the biosynthesis of glucuronoxylomannan (GXM), the main component of capsules, and CAP59deficient strains lose GXM. 46 TLR2 recognizes cryptococcal GXM; 47 thus, the authors indicated that the γδ T cells would not be able to recognize sgl1Δ and would not be activated under conditions lacking TLR2 or the absence of GXM.…”
Section: Whole-cell Vaccines Using Cryptococcal Recombinant Strainsmentioning
confidence: 99%
See 2 more Smart Citations